Thin plate bending analysis using an indirect Trefftz collocation method - Tiago, Carlos M.; Leitão, Vitor M.A.; Vásárhelyi, Anna (Computer Assisted Methods in Engineering and Science, 2023)
In this work, the application of an indirect Trefftz collocation method to the analysis of bending of thin plates (Kirchhoff's theory) is described. The deflection field approximation is obtained with the use of a set of functions satisfying a priori the homogeneous part of the differential equation of the problem. Each of the approximating functions is derived from a known thick plate solution. The boundary conditions are imposed by means of continuous (integral) and discrete (collocation) least squares methods. Numerical examples are presented and the accuracy of the proposed technique is assessed.